Epidemiological profile of syphilis in pregnant women and congenital: historical series from 2011 to 2020 in the Metropolitan Health Region I, state of Pará, Brazil (Research, Society and Development, 2022)
Objective: To describe the epidemiological profile of syphilis in pregnant women (SG) and congenital (SC) in Health Region I, Pará state, Brazil, in the historical series from 2011 to 2020. Methodology: Ecological study of mixed design that aims to analyze the temporal trend and spatial distribution of SG and SC. The data were obtained through the Panel of Epidemiological Indicators of the Ministry of Health. Results: 3038 cases of SG and 1703 cases of SC were reported. Belém had the highest frequency of SG and SC cases, followed, respectively, by Ananindeua, Marituba, Benevides and Santa Bárbara. Significant increases in the incidence of SG were observed in all municipalities in Health Region I (p